2020
DOI: 10.1038/s41433-020-01295-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of Modified Collaborative Ocular Melanoma Study IRIS plaques for treatment of iris, iridociliary, and ciliary body melanoma

Abstract: Background/objectives To report clinical outcomes of modified Collaborative Ocular Melanoma Study IRIS (COMS IRIS) plaques for treatment of iris, iridociliary, and ciliary body melanoma. Subjects/methods Retrospective, single-centre cohort study of iris melanoma treated with COMS IRIS plaque radiotherapy from July 26, 2010 to October 15, 2018. Medical records were reviewed for demographics, tumour features, treatment parameters, and clinical outcomes. Results There were 22 cases, diagnosed at mean age of 59 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…[ 1 ] Our 8% recurrence rate is consistent with existing literature, with post-EPB recurrence reported in 0%–9% of iris melanoma cases. [ 1 9 ] Notably, the single instance of recurrence was a ring melanoma. Ring melanoma can be difficult to detect at initial diagnosis as there may be an area of focal thickening, and the remainder of the ciliary body appears normal; it is a known mechanism of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Our 8% recurrence rate is consistent with existing literature, with post-EPB recurrence reported in 0%–9% of iris melanoma cases. [ 1 9 ] Notably, the single instance of recurrence was a ring melanoma. Ring melanoma can be difficult to detect at initial diagnosis as there may be an area of focal thickening, and the remainder of the ciliary body appears normal; it is a known mechanism of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-specific customization of radiotherapy may also be an avenue to mitigate vision-limiting radiation side effects. In plaque radiotherapy for the management of iris melanoma, custom-shaped plaques based on tumor extent have been used to decrease radiation to unaffected structures [33 ▪ ,34,35,36 ▪ ]. In a study of 22 patients with iris melanoma, Xu et al reported the use of segmental arcs of the dome-shaped traditional Collaborative Ocular Melanoma Study plaque to reduce radiation exposure outside the intended treatment area [33 ▪ ].…”
Section: Advances In Primary Uveal Melanoma Treatmentmentioning
confidence: 99%
“…In plaque radiotherapy for the management of iris melanoma, custom-shaped plaques based on tumor extent have been used to decrease radiation to unaffected structures [33 ▪ ,34,35,36 ▪ ]. In a study of 22 patients with iris melanoma, Xu et al reported the use of segmental arcs of the dome-shaped traditional Collaborative Ocular Melanoma Study plaque to reduce radiation exposure outside the intended treatment area [33 ▪ ]. At 51 months follow-up, the 3-year Kaplan–Meier risk of local tumor recurrence was 7%, with no patients developing systemic metastasis.…”
Section: Advances In Primary Uveal Melanoma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, brachytherapy, using isotopes of iodine-125 (I-125) and ruthenium-106 (Ru-106), is the most commonly used therapeutic approach for uveal melanoma, with a local control rate in the range of 88–98% at five years [ 1 ], and it is equivalent to enucleation in terms of prevention of systemic spread and death [ 2 ]. Consequently, plaque brachytherapy remains the method of choice to control primary intraocular tumors [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%